Criterion validity of the International Physical Activity Questionnaire Short Form (IPAQ-SF) for use in patients with rheumatoid arthritis: comparison with the SenseWear Armband. Issue 2 (June 2015) - Tierney, M.; Fraser, A.; Kennedy, N.
Abstract: Objectives: The International Physical Activity Questionnaire Short Form (IPAQ-SF) is a self-report questionnaire commonly used in patients with rheumatoid arthritis (RA) to measure physical activity. However, despite its frequent use in patients with RA, its validity has not been ascertained in this population. The aim of this study was to examine the criterion validity of energy expenditure from physical activity recorded with the IPAQ-SF in patients with RA compared with the objective criterion measure, the SenseWear Armband (SWA) which has been validated previously in this population. Design: Cross-sectional criterion validation study. Setting: Regional hospital outpatient setting. Participants: Twenty-two patients with RA attending outpatient rheumatology clinics. Interventions: Subjects wore an SWA for 7 full consecutive days and completed the IPAQ-SF. Main outcome measures: Energy expenditure from physical activity recorded by the SWA and the IPAQ-SF. Results: Energy expenditure from physical activity recorded by the IPAQ-SF and the SWA showed a small, non-significant correlation ( r = 0.407, P = 0.60). The IPAQ-SF underestimated energy expenditure from physical activity by 41% compared with the SWA. This was corroborated using Bland and Altman plots, as the IPAQ-SF was found to overestimate energy expenditure from physical activity in nine of the 22 individuals, and underestimate energy expenditure from physical activity in the remaining 13 individuals. Conclusion: The IPAQ-SF has limited use as an accurate and absolute measure for estimating energy expenditure from physical activity in patients with RA.